Model Pembelajaran Kompetitif dalam Meningkatkan Kreativitas Belajar Siswa - M. Yusuf (JIEM: Journal of Islamic Education and Manajemen, 2020)
It is undeniable that student learning motivation both in classroom and at home or in the dormitory always experiences ups and downs, maintaining the stability of their enthusiasm for learning is also one of the responsibilities of the teacher and also the school, so various efforts need to be made to keep them motivated and enthusiasm for learning and always trying to improve it. Various models and styles are found in learning theory, but not necessarily in any place and also in developing cases, because the environment and also typical of students are very diverse, from which a mature understanding is needed if the teacher or school manager wants to apply one of the theory or learning models in schools